MAGNAMOSIS IV: magnetic compression anastomosis for minimally invasive colorectal surgery - Wall, J.; Diana, M.; Leroy, J.; DeRuijter, V.; Gonzales, K. D.; Lindner, V.; Harrison, M.; Marescaux, J. (Endoscopy, 2013)
Background and study aims: MAGNAMOSIS forms a compression anastomosis using self-assembling magnetic rings that can be delivered via flexible endoscopy. The system has proven to be effective in full-thickness porcine small-bowel anastomoses. The aim of this study was to show the feasibility of the MAGNAMOSIS system in hybrid endoscopic colorectal surgery and to compare magnetic and conventional stapled anastomoses. Methods: A total of 16 swine weighing 35 – 50 kg were used following animal ethical committee approval. The first animal was an acute model to establish the feasibility of the procedure. The subsequent 15 animals were survival models, 10 of which underwent side-to-side anastomoses (SSA) and 5 of which underwent end-to-side (ESA) procedures. Time to patency, surveillance endoscopy, burst pressure, compression force, and histology were assessed. Histology was compared with conventional stapled anastomoses. Magnetic compression forces were measured in various anastomosis configurations.Results: Colorectal anastomoses were performed in all cases using a hybrid NOTES technique. The mean operating time was 71 minutes. Mean time to completion of the anastomosis was similar between the SSA and ESA groups. Burst pressure at 10 days was greater than 95 mmHg in both groups. One complication occurred in the ESA group. Compression force among various configurations of the magnetic rings was significantly different (P < 0.05). Inflammation and fibrosis were similar between magnetic SSA and conventional stapled anastomoses. Conclusion: MAGNAMOSIS was feasible in performing a hybrid NOTES colorectal anastomosis. It has the advantage over circular staplers of precise endoscopic delivery throughout the entire colon. SSA was reliable and effective. A minimum initial compression force of 4 N appears to be required for reliable magnetic anastomoses.